A new species and record of Biancolina Della Valle, 1893 (Amphipoda, Senticaudata, Ampithoidae) from the Southwestern Atlantic - Andrade, Renan de Melo (2022)
Here we describe a new species of Biancolina from Pernambuco, Brazil, found in association with the brown algae Sargassum spp., between 0.5 and 1.0 m depth. The new species differs from its congeners mainly by the following combination of characters: antenna 1 twice the length of antenna 2, lacinia mobilis present in both mandibles, article 4 of the maxilliped bulbose; coxa 6 with anteroventral lobe well developed as in posteroventral lobe, peduncle of uropod 1 weakly setose, palm of pereopods 5-7 lacking robust seta. This is the first record of Biancolina from the southwestern Atlantic.